(untitled) (Global Journal of Human-Social Science, 2023)
The investigation focused on identifying analyzing and discussing the results on the level of valorization of this capital For the research a good reading review on people management knowledge management skills and the training and development of people in organizations as well as the legal-legal framework on the Valorization of Human Capital legal instruments as being the main tools in valuing Human Capital According to the research it is people who make up the organic structure of organizations they are the ones who occupy the vacancies that stratify the activities and tasks of public and private organizations